Analisis Peningkatan Kesejahteraan Nelayan Di Kecamatan Koto Tangah Kota Padang - Yolanda Yolanda; Lovelly Dwinda Dahen; Putri Meliza Sari (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2022)
This study aims to analyze: 1) The effect of consumption patterns on income, 2) The effect of education level on income, 3) The influence of entrepreneurial spirit on income, 4) The effect of income on welfare, 5) The effect of consumption patterns on welfare, 6) The effect of education level on welfare, 7) The influence of entrepreneurial spirit on welfare. The method used in this research is two stage least square analysis test. The results show that 1) Consumption patterns have a positive and significant effect on fishermen's income. 2) The level of education has a positive and insignificant effect on income. 3) Entrepreneurial spirit has a positive and insignificant effect on income. 4) Income has a positive and significant effect on welfare. 5) The consumption pattern has a negative and significant effect on welfare. 6) The level of education has a negative and insignificant effect on welfare. 7) Entrepreneurial spirit has a positive and insignificant effect on welfare.